Acute malnutrition and its contributing factors among children under-five years in rural kebeles of Shashemene Oromia, Ethiopia - Shifera, Nigusie; Endale, Aschalew; Debela, Degfachew; Yosef, Tewodros (Frontiers in Nutrition, 2022)
Background: Globally, more than 52 million under-five years old were wasted; One-third of these children live in Africa. Ethiopia is the seventh country among the ten top countries in which acute malnutrition is concentrated and currently 10% of under-five children are wasted. Even though Ethiopia has implemented a variety of nutritional interventions, acute malnutrition is still prevalent and spreading at an alarming rate. Therefore, this study aimed to assess the prevalence of Acute-Malnutrition and its contributing factors among children under-five years of age. Methods: A community-based cross-sectional study was conducted from July 1 to 30, 2018 among twelve randomly selected kebeles. The sample sizes were proportionally allocated to the selected kebeles. A total of 457 mothers/caretakers of under-five children were interviewed using pre-tested structured questionnaires and anthropometric measurements of the children were taken using standard procedures. Epi data version 4.2 was used for data entry and SPSS version 21 was used for statistical analysis. The World Health Organization (WHO) Anthro software was used to convert nutritional data indices. Binary logistic regression was used to determine the association between dependent and independent variables. The level of significance was declared at a p-value less than 0.05. Results: The prevalence of acute malnutrition is 19.91%, (95%CI; 16.24%, 23.57%) among under-five children. Factors contributing to acute malnutrition were mothers with no Antenatal Care (ANC) visits (AOR=2.26, 95% CI 1.14-4.46), mothers who had no autonomy in decision-making (AOR=2.42, 95% CI 1.42-4.12), children with diarrheal disease in the last two weeks preceding the survey (AOR=2.07, 95% CI 1.19-3.59) and not feeding colostrum (AOR=1.99, 95% CI 1.07- 3.71). Conclusion and Recommendation: the prevalence of acute malnutrition is high as compared to other findings in Ethiopia. Moreover, decision-making power, not feeding colostrum, no ANC visit, and a child’s history of diarrhea were independent determinants of acute malnutrition. Therefore, the local health department and health extension workers should consider imparting health education for women on nutritional counseling and timely treatment for children with diarrhea. Empowering women's decision-making is also a key element in addressing wasting among under-five children.